Evolving new drug treatments for faecal incontinence - Maitra, Rudra Krishna (2017)
Faecal incontinence is an embarrassing and socially debilitating condition which is primarily acquired and increases in prevalence with age. Current conservative measures are aimed at dietary modification and changing the consistency of stool with no targeted treatments available to address the underlying cause of incontinence. Surgical treatments are either unsatisfactory or carry significant morbidity.